Post Transplant Lymphoproliferative Disease Isolated to Kidney Allograft - Viviany Pontes de Oliveira; Ronaldo de Matos Esmeraldo; Claudia Maria Costa de Oliveira; Fernando Barroso Duarte; André Costa Teixeira; Tainá Veras de Sandes-Freitas (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Post-transplantation lymphoproliferative disease (PTLD) comprises a heterogeneous group of hematolymphoid proliferations resulting from a monoclonal or polyclonal proliferation of lymphoid cells. The clinical presentation varies according to the affected sites. The gastrointestinal tract and the central nervous system are the most common, and constitutional symptoms are frequent. Isolated allograft involvement is rare. We report a case of polyclonal PTLD isolated in the kidney allograft in a patient who received an HLA-identical living donor seven years before. Noteworthy, this patient did not present constitutional symptoms, and his only clinical manifestation was graft dysfunction, expressed by an increase in serum creatinine and mild proteinuria. The diagnosis was performed through renal biopsy, which showed dense lymphoid interstitial infiltrate. The PTLD was polyclonal, unrelated to Epstein-Bar virus (EBV), and it was successfully treated with chemotherapy, reduced immunosuppression, and sirolimus.